Projeto de intervenção: fisioterapia preventiva na funcionalidade do idoso - Martins, Camilla Soares (Universidade do Vale do Rio dos Sinos, 2014)
The proportion of people aged 60 years and over is growing worldwide. It is estimated that in 2030 in the developed countries the number of elderly will reach 70 million. In Brazil, the projections for the year 2025 indicate that the total population will increase by five times compared to 1950. As one of its consequences, aging brings a gradual and progressive loss of functional capacity. Therefore, the major health adversities associated with aging are the functional impairment and dependence, which results in, amongst others, restriction / loss of ability or difficulty in performing functions related to daily life. It is proven that for this age group physical activity has a positive impact on the health and quality of life. As such, programs targeted to this population are needed to allow people to continue to work according to their abilities and preferences as they age, and to prevent and delay chronic diseases and disabilities. Nevertheless, given the complexity of the aging process and its various consequences, such programs should be developed and maintained by professionals qualified for the care of the elderly. Accordingly, there is a clear need to provide older people with access to this specialized care. Thus, this work aims to create a space for conducting global physical therapy activities for elderly residents of the city of Ivoti / RS, where more than 10% of population is 60 years or more, and there is no place where activities are targeted to the specific needs of this age group. This space tailored to catter for the elderly will offer differentiated and specialized physical activity programs, including as a means of promoting health by actively intervening in their functional capacity and independence. This is an intervention project on the primary, secondary and tertiary preventive, physical therapeutical action for the functional capacity of elderly residents in the city of Ivoti / RS.
Keywords: Fisioterapia; Prevenção; Idoso e funcionalidade; Physical therapy; Prevention; Elderly and functionality